Application of Activated Carbon Derived from Seed Shells of Jatropha curcas for Decontamination of Zearalenone Mycotoxin - Kalagatur, Naveen K.; Karthick, Kumarvel; Allen, Joseph A.; Nirmal Ghosh, Oriparambil Sivaraman; Chandranayaka, Siddaiah; Gupta, Vijai K.; Krishna, Kadirvelu; Mudili, Venkataramana (Frontiers in Pharmacology, 2017)
In the present study, activated carbon (AC) was derived from seed shells of Jatropha curcas and applied to decontaminate the zearalenone (ZEA) mycotoxin. The AC of J. curcas (ACJC) was prepared by ZnCl2 chemical activation method and its crystalline structure was determined by XRD analysis. The crystalline graphitic nature of ACJC was confirmed from the Raman spectroscopy. SEM showed the porous surface morphology of the ACJC surface with high pore density and presence of elemental carbon was identified from the EDX analysis. From BET analysis, SBET, micropore area and average pore diameter of ACJC were calculated as 822.78 (m2/g), 255.36 (m2/g), and 8.5980 (Å), respectively. The adsorption of ZEA by ACJC was accomplished with varying contact time, concentration of ZEA and ACJC, and pH of media. The ACJC has adsorbed the ZEA over a short period of time and adsorption of ZEA was dependent on the dose of ACJC. The effect of different pH on adsorption of ZEA by ACJC was not much effective. Desorption studies confirmed that adsorption of ZEA by ACJC was stable. The adsorption isotherm of ZEA by ACJC was well fitted with Langmuir model rather than Freundlich and concluded the homogeneous process of sorption. The maximum adsorption of ZEA by ACJC was detected as 23.14 µg/mg. Finally, adsorption property of ACJC was utilized to establish ACJC as an antidote against ZEA-induced toxicity under in-vitro in neuro-2a cells. The percentage of live cells was high in cells treated together with a combination of ZEA and ACJC compared to ZEA treated cells. In a similar way, ΔΨM was not dropped in cells exposed to combination of ACJC and ZEA compared to ZEA treated cells. Furthermore, cells treated with a combination of ZEA and ACJC exhibited lower level of intracellular ROS and caspase-3 compared to ZEA treated cells. These in-vitro studies concluded that ACJC has successfully protected the cells from ZEA-induced toxicity by lowering the availability of ZEA in media as a result of adsorption of ZEA. The study concluded that ACJC was a potent decontaminating agent for ZEA and could be used as an antidote against ZEA-induced toxicity.